Production Performance and Serum Biochemical Indices as Influenced by Lysine and Methionine Supplementation to Low Protein Diet in Vanaraja Laying Hens - Mohapatra, Sonali; BABU, LAKSHMAN KUMAR; PANDA, ARUN KUMAR; PANIGRAHI, BHAGIRATHI; Behera, Kumaresh (Indian Journal of Animal Production and Management, 2023)
An experiment was conducted to evaluate the effect lysine and methionine supplementation to low protein diet on production performance and serum biochemical parameters in Vanaraja laying hens. One hundred twenty (n=120), 30-weeks old Vanaraja laying hens were randomly distributed into four dietary treatments with three replicates in each group having 10 birds in each replicate. Four diets were formulated with 2600 kcal/kg of metabolizable energy (ME) and 13% crude protein (CP). The dietary treatments were: T1- diet contains 0.65% lysine and 0.28% methionine; T2- diet contains 0.70% lysine and 0.32% methionine; T3- diet contains 0.75% lysine and 0.36% methionine and T4- diet contains 0.80% lysine and 0.40% methionine. Body weight and its changes, Hen Housed Egg Production (HHEP), egg weight (g), egg mass (g/day), and feed conversion ratio and serum biochemical parameters found significantly (P<0.05) differed across the dietary treatments during different phases of the experimental period. There was significant (P<0.05) effect of lysine and methionine on the overall body weight gain. Serum biochemical parameters like albumin, globulin, creatinine, uric acid, triglycerides and AST activity varied due to supplementation of EAAs to low CP diet. So it was concluded that diet containing 0.65% lysine and 0.28% methionine (T1) is adequate for optimum production performance and serum biochemical indices in Vanaraja laying hens.